1937
DOI: 10.1152/ajplegacy.1937.120.4.744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hexylresorcinol Upon the Absorption of Insulin From the Gastro-Intestinal Tract of Dogs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1938
1938
1940
1940

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In previous reports one of us (M) and his associates (1,2) have shown that hexylresorcinol aids in the absorption of insulin from the gastrointestinal tract of dogs. It has since been shown that other derivatives, the octyl and heptyl resorcinols (3) and the pentyl, butyl, and propyl resorcinols likewise are active in this physiologic process; the last two, however, less so than the higher compounds.…”
mentioning
confidence: 99%
“…In previous reports one of us (M) and his associates (1,2) have shown that hexylresorcinol aids in the absorption of insulin from the gastrointestinal tract of dogs. It has since been shown that other derivatives, the octyl and heptyl resorcinols (3) and the pentyl, butyl, and propyl resorcinols likewise are active in this physiologic process; the last two, however, less so than the higher compounds.…”
mentioning
confidence: 99%